International Unionism’s Competitive Edge: FIFPro and the European Treaty - Dabscheck, Braham (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2003)
AbstractGlobalization and neo-liberalism have been associated with a decline in unions. In seeking to respond to these problems, unions could cooperate internationally. The orthodoxy among industrial relations scholars is that the European Treaty is antithetical to international unionism because of various provisions which promote competition. The experience of the International Federation of Professional Footballers’ Associations (FIFPro) contradicts this orthodoxy. In August 2001, FIFPro entered into a framework collective bargaining agreement with Fédération Internationale de Football Association (FIFA) on a new set of rules to govern the worldwide employment of professional footballers. Football’s transfer and compensation system violated competitive provisions, in particular the freedom of movement of workers, contained in the European Treaty. Following the 1995 decision of the European Court of Justice in Bosman, and strategic interventions by the European Commission, FIFA sought an accommodation with FIFPro, to protect its new employment rules from further legal attack.